2021
DOI: 10.1039/d0se01385d
|View full text |Cite
|
Sign up to set email alerts
|

Effective electrode design and the reaction mechanism for electrochemical promotion of ammonia synthesis using Fe-based electrode catalysts

Abstract: The electrochemical promotion of ammonia formation on Fe-based electrode catalysts is investigated using proton-conducting-electrolyte-supported cells of H2–Ar, Pt |BaCe0.9Y0.1O3 (BCY)| Fe-based catalysts, H2–N2 at temperatures between 550˚C and 600˚C, and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…The results are summarized as follows: (1) the ammonia formation rate has a positive correlation with H 2 partial pressure in the cathode, which agrees with the previous study. 38 (2) α and β do not change after applying different voltages, which indicates that the reaction mechanism is probably the same as that at the rest potential (surface reaction). (3) The contribution of surface reaction with EPOC to ammonia formation rate is larger than that of charge-transfer reaction with porous pure Fe, and the ammonia formation rate promoted by EPOC can be improved by increasing H 2 partial pressure in the cathode.…”
Section: Resultsmentioning
confidence: 91%
See 3 more Smart Citations
“…The results are summarized as follows: (1) the ammonia formation rate has a positive correlation with H 2 partial pressure in the cathode, which agrees with the previous study. 38 (2) α and β do not change after applying different voltages, which indicates that the reaction mechanism is probably the same as that at the rest potential (surface reaction). (3) The contribution of surface reaction with EPOC to ammonia formation rate is larger than that of charge-transfer reaction with porous pure Fe, and the ammonia formation rate promoted by EPOC can be improved by increasing H 2 partial pressure in the cathode.…”
Section: Resultsmentioning
confidence: 91%
“…In our recent study, 38 we reported the following results: (1) a cathode structure with short triple phase boundary (TPB) length (i.e., porous pure Fe cathode) had better performance of ammonia formation rate than that with long TPB length (i.e., Fe-BCY cermet cathode), (2) the ammonia formation rate had a strong correlation with the H 2 partial pressure in the cathode. The ammonia formation rate increased from 2.2 Â 10 À9 mol cm À2 s À1 (71 mg mg À1 h À1 ) in 10% H 2 -90% N 2 to 1.4 Â 10 À8 mol cm À2 s À1 (450 mg mg À1 h À1 ) in 50% H 2 -50% N 2 using porous pure Fe cathode at 550 C and À1.2 V, which is equivalent to that in the Haber-Bosch process (250-976 mg mg À1 h À1 at 7-10 MPa and 400 C).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“… 17 Recently, we proposed the formation of an effective double layer during NH 3 electrosynthesis with Fe/BaCeO 3 , which can be considered as an extension of the TPB active site model. 18 Several researchers have investigated the metal–support interaction in the electrochemical reaction and noted some similarities between this interaction and the electrochemical promotion effect. 19 An understanding of the complex relationship between these two factors is important for enhancing the electrochemical catalysis process.…”
Section: Introductionmentioning
confidence: 99%